Early-Mid Pleistocene genetic differentiation and range expansions as exemplified by invasive Eurasian Bunias orientalis (Brassicaceae) indicates the Caucasus as key region. Issue 1 (December 2017) - Koch, Marcus; Michling, Florian; Walther, Andrea; Huang, Xiao-Chen; Tewes, Lisa; Müller, Caroline
Abstract Turkish Warty cabbage, Bunias orientalis L. (Brassicaceae) is a perennial herb known for its 250 years of invasion history into Europe and worldwide temperate regions. Putative centers of origin were debated to be located in Turkey, the Caucasus or Eastern Europe. Based on the genetic variation from the nuclear and plastid genomes, we identified two major gene pools in the Caucasian-Irano-Turanian region and close to the Northern Caucasus, respectively. These gene pools are old and started to diverge and expand approximately 930 kya in the Caucasus. Pleistocene glaciation and deglaciation cycles favoured later expansion of a European gene pool 230 kya, which was effectively separated from the Caucasian-Irano-Turanian gene pool. Although the European gene pool is genetically less diverse, it has largely served as source for colonization of Western and Northern Europe in modern times with rare observations of genetic contributions from the Caucasian-Irano-Turanian gene pool such as in North-East America. This study largely utilized herbarium material to take advantage of a biodiversity treasure trove providing biological material and also giving access to detailed collection information.